Acute Respiratory Distress Syndrome after Rotavirus Infection in a C1q Nephropathy Patient: A Case Report - Hye Jin Kim; Jeesu Min; Ji Hyun Kim; Yu Hyeon Choi; Mi Seon Han; Il-Soo Ha; Hee Gyung Kang (Korean Society of Pediatric Nephrology, 2021)
C1q nephropathy is a rare glomerulopathy that typically presents with nephrotic syndrome in children. Treatment with immunosuppressive agents renders patients vulnerable to infection and its complications. Gastroenteritis is common in children, and rotavirus is a leading cause. Extraintestinal manifestations of rotavirus have recently been reported; however, there is a paucity of cases exploring the involvement of a rotavirus on the respiratory system. Acute respiratory distress syndrome (ARDS) is a rapid onset respiratory failure characterized by noncardiogenic pulmonary edema and hypoxemia. Causes of ARDS include sepsis, pneumonia, pancreatitis, aspiration, and trauma. In this paper, we report a case of ARDS after rotavirus infection in a child with C1q nephropathy who had been treated with immunosuppressive agents.